Measuring the impact of disability benefits: a feasibility study - Richard Berthoud (University of Essex, Institute for Social and Economic Research (ISER), 2009)
Social security benefits designed to meet the extra costs faced by disabled people have been in place since the early 1970s, and currently cost nearly 15 billion per year. Over the period the benefits have enjoyed bilateral political support, and the only major changes (eg in 1992) have been to extend entitlement and increase expenditure. But remarkably little is known about the impact of these benefits exactly what difference they make to claimants care and mobility arrangements, to their overall standard of living, and to their social inclusion and sense of identity. The Department for Work and Pensions is considering how to study the impact of disability benefits in more depth. The Department has commissioned this feasibility study, to summarise the questions and assess alternative research approaches, with a view to launching more detailed investigations.
Keywords: 330